PENGARUH DIGITAL MARKETING DAN PEROLEHAN INVESTOR BARU (LENDER) (STUDI KASUS PADA PT. ALAMI FINTEK SHARIA) - Amri Marihot Jati; Nova Novita (Journal of Accounting, Management and Islamic Economics, 2025)
This purpose of this research is to examine the impact of digital marketing costs, namely Search Engine Marketing (BSEM) and Social Media Marketing (BSMM) costs on the acquisition of New Investors (Lenders) and Revenue then analyze the effectiveness of digital marketing activities at PT. ALAMI Fintek Sharia for the 2020-2021 period. The data is obtained from secondary digital marketing reports and ALAMI marketplace fee reports for the 2020-2021 period. The analysis technique used nin this research is multiple regression linear analysis. The hypothesis in this study is based on the phenomenon of the problem that occurs in ALAMI, as well as previous research and other supporting theories. The results of this study provide evidence that BSEM and BSMM have a positive effect on the acquisition of New Investors (Lenders), but have no effect on Revenue (Revenue), this study also provides evidence that digital marketing activities at ALAMI have been effective in achieving the specified target. Based on the results of this study, one of the research suggestions to PT ALAMI Fintek Sharia is to increase BSEM and BSMM budgeting so that companies are able to maximize and utilize their digital marketing in order to achieve the level of acquisition of New Investors (Lenders) with more and other company targets.